1996
DOI: 10.1111/j.1476-5381.1996.tb15445.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytosolic calcium in skeletal muscle cells of the mdx mouse under conditions of stress

Abstract: 1 In Duchenne muscular dystrophy (DMD) dysregulation of cytosolic calcium appears to be involved in the degeneration of skeletal muscle fibres. Therefore, we have studied the regulation of the free cytosolic calcium concentration ([Ca2+]) under specific stress conditions in cultured myotubes isolated from the hind limbs of wild-type (C57BL10) and dystrophin-deficient mutant mdx mice. [Ca2+] [Ca2+]c when the cells were exposed to the hypo-osmotic buffer (100 mOsm).5 Incubation of the cell culture for 3-5 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 45 publications
(55 reference statements)
4
48
1
1
Order By: Relevance
“…It should be noted that although the present and other studies (7,37,40,45) are consistent with SOCE in skeletal muscle cells, the influence of glucocorticoids on muscle calcium entry and concentrations has been examined only in a few previous studies, with apparently conflicting results (41,51,57,74). The present finding of increased calcium entry and concentrations in muscle cells treated with dexamethasone is consistent with a report by Vandebrouck et al (74).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It should be noted that although the present and other studies (7,37,40,45) are consistent with SOCE in skeletal muscle cells, the influence of glucocorticoids on muscle calcium entry and concentrations has been examined only in a few previous studies, with apparently conflicting results (41,51,57,74). The present finding of increased calcium entry and concentrations in muscle cells treated with dexamethasone is consistent with a report by Vandebrouck et al (74).…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, the effects of glucocorticoids on SOCE were not determined in the reports by Ruegg and coworkers (41,51,57). The reason(s) for the conflicting results is not apparent but may be related to species differences, human muscle cells being studied by Vandebrouck et al (74) and mouse myocytes being used by Ruegg and coworkers (41,51,57).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…There is some controversy about this Ca 2ϩ elevation (1,4). Some groups (5,6) showed that basal cytosolic Ca 2ϩ concentration ([Ca 2ϩ ] c ) 1 was higher in dystrophic skeletal muscle cells relative to controls, whereas other laboratories (7,8) found that [Ca 2ϩ ] c was only increased under stress. To elucidate this contention, the redistribution of Ca 2ϩ into intracellular organelles should be examined.…”
Section: Exchanges During Kcl Depolarization These Newly Demonstratementioning
confidence: 99%